2022
DOI: 10.5539/jps.v11n1p10
|View full text |Cite
|
Sign up to set email alerts
|

Adaptative Leaf Morphology of Eurya japonica Thunb. (Ternstroemiaceae) in Serpentine Areas

Abstract: Serpentine soils are known to affect plant growth and plants in these soils have morphological and anatomical modifications. Comparative leaf morphology and anatomy studies of Eurya japonica Thunb. was conducted between serpentine and inland (control) areas. Our morphological analyses revealed that the individuals in the serpentine areas had significantly smaller and thicker leaves than those in the inland areas. Our anatomical analyses showed that the smaller leaves of serpentines had decreased numbers of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
(49 reference statements)
1
8
0
Order By: Relevance
“…Moreover, our anatomical results showed that no single parameter, such as the adaxial and abaxial epidermal cells, palisade tissue, or spongy tissue contributed to the increased leaf thickness of serpentine L. japonicum; however, all of them were slightly higher than plants of the inland populations. These anatomical results were also similar to those of E. japonica (Shiba et al, 2022), where the modification in leaf thickness, when woody species adapted from inland to serpentine areas, was related to the change in the height of each cell.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Moreover, our anatomical results showed that no single parameter, such as the adaxial and abaxial epidermal cells, palisade tissue, or spongy tissue contributed to the increased leaf thickness of serpentine L. japonicum; however, all of them were slightly higher than plants of the inland populations. These anatomical results were also similar to those of E. japonica (Shiba et al, 2022), where the modification in leaf thickness, when woody species adapted from inland to serpentine areas, was related to the change in the height of each cell.…”
Section: Discussionsupporting
confidence: 84%
“…serpentine ones (Hayakawa et al, 2012;Ohga et al, 2012;Kumekawa et al, 2013;Shiba et al, 2022). As mentioned above, the speciation of serpentine-adapted inland species seems to be associated with leaf morphology and the stomatal density and/or size.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations